Trends in the Use of Sphingosine 1 Phosphate in Age-Related Diseases: A Scientometric Research Study (1992-2020) - Qiong He; Gaofeng Ding; Mengyuan Zhang; Peng Nie; Jing Yang; Dong Liang; Jiaqi Bo; Yi Zhang; Yunfeng Liu (Journal of Diabetes Research)
Objectives. This study was designed to explore the intellectual landscape of research into the application of sphingosine 1 phosphate (S1P) in age-related diseases and to identify thematic development trends and research frontiers in this area. Methods. Scientometric research was conducted by analyzing bibliographic records retrieved from the Web of Science (WOS) Sci-Expanded Database dated between 1900 and 2020. Countries, institutions, authors, keyword occurrence analysis, and cooperation network analysis were performed using the CiteSpace and VOSviewer software. Results. A total of 348 valid records were included in the final dataset, and the number of publications and the frequency of citations have grown rapidly over the last ten years. The USA (n=175), China (n=42), and Germany (n=37) were the three largest contributors to the global publications on S1P and aging, while the Medical University of South Carolina (n=15), University of California, San Francisco (n=13), and University of Toronto (n=13) were the leading institutions in this field. Analysis showed that early studies primarily focused on the mechanism of S1P intervention in AD. While S1P and its relevant metabolites have remained a long-term active area of research, recent studies have focused more on interventions aimed at improving retinal degeneration, cardiomyopathy, multiple sclerosis, and diabetes, among others. Conclusions. It is worth mentioning that this manuscript is the first to describe any bibliometric analysis of S1P and its application in age-related interventions. This study includes a discussion of the (1) historical overview of the topic; (2) main contributors: journals, countries, institutes, funding agencies, and authors; (3) collaboration between institutes and authors; (4) research hot spots and zones; and 5) research trends and frontiers. This will enable scholars to understand the current status of S1P research in age-related diseases.